Actively Q-switched Nd:YLF laser emitting at 908 nm. (24th November 2021) - Zhang, Jiale; Ma, Jian; Lu, Tingting; Zhu, Xiaolei
Abstract: An actively Q-switched quasi-three-level Nd:YLF laser emitting at 908 nm, for the first time to our knowledge, was demonstrated. A RTP double-crystal scheme was used to realize electro-optical Q-switcher, and a L-shaped cavity structure was designed to suppress parasitic oscillation at 1047 nm. An 806 nm laser diode was used as the pump source with about 480 μ s pulse width. With 46.4 mJ pump pulse energy input at repetition rate of 100 Hz, maximum output pulse energies of 0.84 mJ and 0.73 mJ were obtained with output transmissions of 6.5% and 11%, respectively. The corresponding peak pulse powers were up to 14.3 kW and 12.1 kW, and the output pulse widths were 58.6 ns and 60.3 ns. The central laser wavelengths were both at 908.3 nm with spectral bandwidth of over 0.7 nm.